ACHIEVEMENT IN ORGANIZING THAI ETIQUETTE LEARNING ACTIVITIES: ROLE PLAY - Phramaha Arnon Arnando; Sanya Sodprasert; Pusadee Jirawatanakit; Phramaha Songkhram Chantakir; Phra Khatha Sakarawo (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2019)
This research was done with the objectives 1) to study some learning activities by using role-plays, 2) to study the accomplishment on Thai tradition concerning with Thai manners of secondary school in first year from Taweewattana School Yannawa district Bangkok.Population sampling was one class for 13 persons. Its tools were 1) lersrning plan, activities on role-plays on the Thai manners with 4 papers of plan and 4 hours, 2) testing formation on the students’ accomplishment before and after learning was kinds of choices a,b,c,d around 40 items. Its results were found that students had learnt the contents in the new method with role-plays. 1) They were interested in lessons and developed their skills on procedures of such that learning by the real action on Thai manner such as Thai greeting, dress, conversation meeting in various occasions. with reserving Thai tradition. 2) Analitical results had the compared score with learning achievement before and after. They felt happy and funny in learning with the role-plays because it made them understand better and it effected to testing after learning they have got higher marks than before learning in 40 items of test. The means had score at 30.69. After learning along with 4 plans completely, they had got the 40 items of test. The means had score at 34.77. The achievement after learning with some higher means before learning was significant at lavel 0.05.